MENINGKATKAN KEMAMPUAN BERBICARA ANAK MELALUI METODE BERCERITA DENGAN MEDIA BONEKA PADA ANAK USIA 4-5 TAHUN DI PAUD TASA CHANTIKA DESA KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Tamsil Tamsil; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is to improve the ability to talk about the child to communicate smoothly as the recounts, the child may not be able to speak with their own words, children are not able to express a desire to speak a simple sentence, the child has not been able to answer questions from the teacher until the author try to use the media in a way that pulling the puppet in an effort to improve speaking skills of children aged 4-5 years through the use of puppets. This type of research is a classroom action research conducted by two cycles, each cycle consisting of the stages of planning, action, observation and reflection. Sheets based on observation of the child candy 58 in 2009. The number of subjects in this study were 10 children ranging from 5 boys and 5 girls. The collection of data on research carried out in the second semester of the year 2015/2016, through the instrument of data collection in the form of sheets observation teachers and observation of the child. Data taken from the results of the evaluation at the end of each cycle. The study involved a man peers as observers. Based on the data obtained and the percentage of the first cycle is 25% and the percentage of the second cycle was 96%, thus it can be concluded through storytelling can enhance speech-age children 4-5 years in early PAUD Tasa Chantika Desa Kubang Jaya Kecamatan Siak Hulu District Kampar.Key Words: Speech, The Story